Pengaruh Strategi Pembelajaran Berdiferensiasi terhadap Hasil Belajar IPAS Siswa Kelas V SDN Sawah Besar 01 - Livia Istiqomah; Fine Reffiane; Donis Sanjaya (Departement of Mathematics Education, 2024)
This study aims to determine the improvement in learning outcome IPAS of fifth grade students at SDN Sawah Besar 01 before and after implementing differentiated learning strategies. The research design used in this study is a quantitative experiment with a one-group pre-test and post-test model. The subjects in this study were 28 fifth grade students at SDN Sawah Besar 01. The instrument used to measure student learning outcomes is the pre-test and post-test scores. The results of the study show that before the implementation of differentiatied learning strategies, the average score was 58, while after the implementation of differentiatied learning strategies, the average score increased to 84. Based on the t-test results, it is shown that differentiatied learning strategies have an influence on student learning outcomes with a significant value of <0,05. In addition, the N-Gain criteria also obtained a value 0f >0,03, indicating that differentiatied learning strategies have a high level of effectiveness. Therefore, it can be concluded that differentiatied learning strategies have an effect on the learning outcomes of fifth grade students at SDN Sawah Besar 01 in the IPAS subject.